Paediatric spinal conditions. Issue 6 (June 2020) - Tomlinson, James E; Gummerson, Nigel W
Abstract: Children with spinal problems present to a wide range of healthcare providers. These providers include the emergency department, their GPs, physiotherapy and the paediatric medical and surgical clinics (including orthopaedics). They may present with a variety of symptoms, but the common complaints are: back pain, leg pain or a change in back shape (spinal deformity). Some children may experience a combination of these problems. A systematic approach to the history and examination with knowledge of the common spinal conditions in children will allow you to select the best investigations. This will maximize the chance of making the correct diagnosis and providing appropriate care. This article aims to give an overview, appropriate for surgeons in the early years of their training.